2019
DOI: 10.1002/hep.30232
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Fenestrae Dynamics in Live Murine Liver Sinusoidal Endothelial Cells

Abstract: No other multimodal biomedical high-resolution imaging technique to-date has allowed collecting new fine structural information on the lifespan, formation, and disappearance of LSEC fenestrae. By doing so, we gathered also evidence of three different pathways implemented in the loss of fenestrae that result in defenestrated LSECs. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 39 publications
(100 reference statements)
3
64
0
Order By: Relevance
“…Our recent work demonstrated that even better insight into the dynamics of the fenestra structure could be achieved using multimodal AFM imaging. Dynamically tracking the detailed structure and dynamics of the fenestrae in vitro for the first time in living (ie, nonfixed) LSECs, enabled us to obtain time‐dependent high‐resolution images of the actin cytoskeleton that supports the fenestrae, confirming the previously reported fenestrae‐associated cytoskeletal structures . We showed that some FACRs are closed, that is, filled with lipid membrane, while others are open .…”
Section: Introductionsupporting
confidence: 84%
See 4 more Smart Citations
“…Our recent work demonstrated that even better insight into the dynamics of the fenestra structure could be achieved using multimodal AFM imaging. Dynamically tracking the detailed structure and dynamics of the fenestrae in vitro for the first time in living (ie, nonfixed) LSECs, enabled us to obtain time‐dependent high‐resolution images of the actin cytoskeleton that supports the fenestrae, confirming the previously reported fenestrae‐associated cytoskeletal structures . We showed that some FACRs are closed, that is, filled with lipid membrane, while others are open .…”
Section: Introductionsupporting
confidence: 84%
“…Dynamically tracking the detailed structure and dynamics of the fenestrae in vitro for the first time in living (ie, nonfixed) LSECs, enabled us to obtain time‐dependent high‐resolution images of the actin cytoskeleton that supports the fenestrae, confirming the previously reported fenestrae‐associated cytoskeletal structures . We showed that some FACRs are closed, that is, filled with lipid membrane, while others are open . Those findings underlay the need for the coexistence of some structural proteins, other than actin, for maintaining and switching the fenestrae in an open vs closed state.…”
Section: Introductionsupporting
confidence: 84%
See 3 more Smart Citations